Training and Mentoring in Developing Production SOPs for Tofu Agroindustries in Badas Village, Kediri Regencyy: Pelatihan Penyusunan SOP Produksi Agroindustri Tahu di Desa Badas Kabupaten Kediri - Satriya Bayu Aji; Agustia Dwi Pamujiati; Reksa Nanda Prayoga; Kevin Dyo Pamungkas; Kharisma Satria Pamungkas; Taufan Achmad Ghozali Yusuf (Lembaga Riset dan Inovasi Masyarakat Madani, 2026)
Many tofu producers in Badas Village still rely on habitual production practices and do not yet have a written standard operating procedure (SOP), which may lead to inconsistent work processes and weak quality control. This community service program aimed to improve the understanding and capacity of tofu producers in preparing a production SOP for tofu agroindustry in Badas Village, Badas District, Kediri Regency. The program was conducted from January to March 2026 with around 30 participants using a participatory approach through preparation, socialization, training, mentoring, and evaluation. The evaluation was conducted by comparing participants’ understanding scores before and after the activity as an internal program indicator, supported by field observations, discussion notes, and activity documentation. The results showed that the partners initially had no written production SOP, work stages varied among workers, and simple quality control had not been implemented systematically. Through this program, an applicable production SOP draft was developed as a shared work guideline, and participants’ understanding score increased from 60 to 85. Overall, this activity produced an applicable production SOP draft, strengthened partners’ understanding of process standardization, and provided an initial basis for improving hygiene and sanitation, production recording, and household food licensing readiness.